The how : notes on the great work of meeting yourself - Daley-Ward, Yrsa (UK : Penguin Books, 2021)
"From the acclaimed poet behind bone, an exploration of how we can meet our truest selves, the ones we've always been meant to become Yrsa Daley-Ward's words have resonated with hundreds of thousands of readers--through her books of poetry and memoir, bone and The Terrible; through her writing for Beyoncé on Black Is King; and through her always illuminating Instagram posts. Now, in The How, Yrsa encourages readers to begin, as she puts it, the great work of meeting ourselves. This isn't the self we've built up in response to our surroundings, or the self we manufacture to please the people around us, but instead, our most intimate self, the one we visit in dreams, the one that calls to us from a glimmering future. With a mix of short lyrical musings and her signature stunning poetry, Yrsa gently takes readers by the hand, encouraging them to join her as she explores how we can remove our filters, and see and feel more of who we really are behind the preconceived notions of propriety and manners we've accumulated with age. With a beautiful design and intriguing meditations, The How can be used to start conversations, to prompt writing, to delve deeper--whether you're solo, or with friends, on your feet or writing from the solace of home"--
Keywords: Self-actualization (Psychology); Mind and body